A study of how ICT capabilities can influence dynamic capabilities. Issue 2 (7th March 2016) - Parida, Vinit; Oghazi, Pejvak; Cedergren, Stefan
Abstract : Purpose: – Prior studies have argued that small firms with dynamic capabilities can revise and reconfigure their internal resources to meet the uncertainties of their business environment. However, there is a lack of understanding of how they can develop such critical capabilities. The purpose of this paper is to propose that small firms can employ information and communication technology (ICT) capabilities as a facilitator for developing dynamic capabilities. Thus, the study builds on resource-based view (RBV) literature and information systems (IS) literature by examining the influence of ICT capabilities on the dynamic capabilities of small firms. Design/methodology/approach: – Several hypotheses were tested by analysing the survey data from 291 small high-technology firms in Sweden. Findings: – The results reveal that ICT capabilities influence dynamic capabilities of small firms. More specifically, the ICT use for internal efficiency positively influences adoptive capabilities, collaborative use of ICT positively influences networking capabilities, and ICT use for communications positively influences both adaptive and innovation capabilities. Consequently, the results suggest that the different components of ICT capabilities facilitate the development of the different organizational capabilities that together represent dynamic capabilities and thus, can contribute to a small firm's competitive advantage. Practical implications: – This study has few implications for the managers and CEO's of small high-technology firms. First, by prioritizing ICT capabilities, small firms can benefit from the development of dynamic capabilities that will support them to meet the challenges of turbulent business environment. Second, because small firms usually lack internal resources (i.e. financial resources and competence), the study provides more specific direction on how they can strategically invest and build different components of ICT that will positively influence their adaptive, absorptive, innovative, and network capabilities. Originality/value: – The study provides an alternative view of how ICT capabilities influence the performance of small firms, and outlines how such capabilities influence the development of dynamic capabilities. Therefore, the study in hand contributes to the RBV and IS literature by specifically linking the components of ICT capabilities to dynamic capabilities and its related sub-capabilities.